Efektivitas Pengelolaan Dana Desa Dalam Pembangunan Infrastruktur Di Desa Mekar Sekuntum - pribadi, windi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This study uses a qualitative approach with a total of 6 (six) speakers consisting of the Village Head, Village Secretary, General Chairperson of the Farmer Group, and the people who live in Mekar Sekuntum Village. There are 2 (two) types of data used, namely primary data in the form of direct interviews with sources and secondary data obtained from the Mekar Sekuntum village office and the Central Statistics Agency of Sambas Regency. The method used in the analysis is using the calculation of the effectiveness ratio to measure the level of effectiveness and using RI Law no. 6 of 2014 concerning Villages, Permendagri No. 113 of 2014 concerning the Management of Village Funds and Perbup Sambas No. 48 of 2018 concerning Village Fund Management to measure the effectiveness of Village Fund management. The results of this study indicate that the effectiveness of the Village Fund in Mekar Sekuntum Village in 2020 is declared effective using an effectiveness ratio with a score of 99.99% and in 2021 it is declared very effective with a score of 100%. For development in 2020 it is declared effective with a score of 96.80% and 2021 is also declared effective with a score of 99.99%. Meanwhile, agriculture in 2020 was declared ineffective with a score of 0.00% and in 2021 it was declared effective with a score of 99.99%. Meanwhile, the management of the Village Fund is stated to have been in accordance with RI Law Number 6 of 2014 concerning Villages, Minister of Home Affairs Regulation Number 113 of 2014 concerning Village Financial Management and Sambas Regent Regulation Number 48 of 2018 concerning Village Financial Management.